THE LITHOLOGY OF FLOOD PRONE AREAS USING THE VERTICAL ELECTRICAL SOUNDING (VES) METHOD - Sinaga, Jesika Erni ELfrita; Budianto, Geri; Pritama, Vinki Loverly; Suhendra, Suhendra (Universitas Mataram, 2023)
Rock lithology modeling of flood-prone areas has been carried out using the Vertical Electrical Sounding (VES) method in Rawa Makmur village, Bengkulu city. Field data acquisition using a stretch length of 160 with the MAE X612-EM Geoelectric tool forming a straight line. VES method, using Excel software for resistivity variations with depth and Progress lithology modeling. This research aims to determine the subsurface condition of flood-prone areas and the characteristics of rocks that make up flood-prone areas. The results of this study can be concluded that the Rawa Makmur village is dominated by sand (0,2-50 Î©m), silty sand (1-35 Î©m), gravel sand (20-150 Î©m) and clay (65-250 Î©m) at several points. VES 1, VES 2, VES 3, VES 4, VES 5, VES 8, and VES 9 have a shallow water table of 1-10 meters, close to the Rawa Makmur river and have a rock structure that is saturated with water so that it cannot absorb moisture on the surface and becomes a flood puddle. The characteristics of rocks that make up flood-prone areas are porous stones such as sand and gravel saturated with water. Sites that are not prone to flooding in the Rawa Makmur village at points VES 6 and VES 7 are dominated by the rock structure of sand (20-65 Î©m), gravel sand (100-200 Î©m), and dry gravel (100-1000 Î©m).